2015
DOI: 10.1038/srep13828
|View full text |Cite
|
Sign up to set email alerts
|

TSC2 mediates hyperosmotic stress-induced inactivation of mTORC1

Abstract: mTOR complex 1 (mTORC1) regulates cell growth and metabolism. mTORC1 activity is regulated via integration of positive growth-promoting stimuli and negative stress stimuli. One stress cells confront in physiological and pathophysiological contexts is hyperosmotic stress. The mechanism by which hyperosmotic stress regulates mTORC1 activity is not well understood. We show here that mild hyperosmotic stress induces a rapid and reversible inactivation of mTORC1 via a mechanism involving multiple upstream signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 58 publications
3
25
0
Order By: Relevance
“…Thapsigargin treatment caused a significantly smaller translational effect on individual proteins than the other treatments, suggesting potential differences in translational control ( Figure 4F). Indeed, we found NaCl and arsenite to lead to decreased phosphorylation of the mTORC1 substrate EIF4EBP1 ( Figure 4G), consistent with previous publications (Andreev et al, 2015;Plescher et al, 2015). Thus, the observed translatome differences by thapsigargin versus NaCl or arsenite treatments may be driven by mTORC1.…”
Section: Mtorc1 and Eif2a Attenuate Translation Of Overlapping Proteisupporting
confidence: 91%
“…Thapsigargin treatment caused a significantly smaller translational effect on individual proteins than the other treatments, suggesting potential differences in translational control ( Figure 4F). Indeed, we found NaCl and arsenite to lead to decreased phosphorylation of the mTORC1 substrate EIF4EBP1 ( Figure 4G), consistent with previous publications (Andreev et al, 2015;Plescher et al, 2015). Thus, the observed translatome differences by thapsigargin versus NaCl or arsenite treatments may be driven by mTORC1.…”
Section: Mtorc1 and Eif2a Attenuate Translation Of Overlapping Proteisupporting
confidence: 91%
“…In addition, by studying the effect of other stresses on TSC2 localization, such as hyperosmotic stress, energetic stress, hypoxia and changes in pH, we find that all of them affect TSC2 localization (for hyperosmotic stress, see also ref. 49 ). This suggests that regulation of TSC2 localization is a universal mechanism by which stresses regulate TSC2.…”
Section: Discussionmentioning
confidence: 99%
“…The pcDNA3-FLAG-hRagA and hRagC expression vectors were described previously 4 . A similar vector expressing FLAG-tagged firefly luciferase was used as a negative control (pcDNA3-FLAG-Luc), and is described elsewhere 49 . The integrity of all constructs was verified by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that under hyperosmotic stress NLK, similarly to under oxidative stress, mediates mTORC1 suppression by phosphorylating RAPTOR at Ser863 to disrupt the RAPTOR‐Rag interactions . Moreover, hyperosmotic stress can also inactivate AKT, likely via a Calyculin‐A‐sensitive phosphatase, to promote TSC2 activation, thereby suppressing mTORC1 . Interestingly, hyperosmotic stress was reported to cause sequestration of both mTORC1 and the dual specificity tyrosine‐phosphorylation‐regulated kinase 3 (DYRK3) into SGs .…”
Section: Diverse Extracellular and Intracellular Cues Regulate Mtorc1mentioning
confidence: 99%